Anhalt’s Oppenheimer: The History of a Never-Finished Major Work - Beckwith, John (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2013)
The “opera fantasy” Oppenheimer by Istvan Anhalt (1919–2012) survives as a draft libretto and 1,100 pages of musical sketches, on which the composer concentrated from mid-1988 to late 1991, partly with the collaboration of the playwright John Murrell. Prolonged negotiations with the Canadian Opera Company eventually collapsed and the work was abandoned. Using prior research by Peter Laki and archival documents (especially the composer’s previously inaccessible “diary” of the opera’s progress), this article traces Oppenheimer’s compositional development and the COC production talks, compares it to the 2005 opera Doctor Atomic by John Adams and Peter Sellars (both works deal with J. Robert Oppenheimer’s role in creating the first atomic bomb), and speculates on possible affinities between the existing sketches and other Anhalt compositions of the same period.